Metode Syarh Hadis Mursal Dalam Kitab Awjaz Al-Masālik Ilā Muwaththa’ Mālik Karya Syekh Muhammad Zakariyyā Al-Kāndahlawiyy - Hasan, Muhammad; Majid, Latifah Abdul; Othman, Fadhlan Mohd; Sakat, Ahamad Asmadi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
Before the arrival of the shahīh al-Bukhārī and shahīh Muslim, the Muslim people were more familiar with the kitab al-Muwaththa Imam Mālik. Kitab al-Muwaththa’ is a book that contains the Hadith and fiqh of the Mālic imam school. The Kitab al-Muwaththa’ is known as a book that contains many mursal hadiths. Many scholars after the death of imam Mālik tried to give commentary to the kitab al-Muwaththa’ according to their respective scientific backgrounds. Some give commentary in terms of hadith science, some give commentary from fiqh, and some try to propose hadiths in it that are considered unconnected. One of the hadith scholars who took part in giving syarah to this book was Syekh Muhammad Zakariyyā al-Kāndahlawiyy (1315-1402H/1898-1982). He is a 20th-century hadith scholar who is often a reference for Muslim scholars. One of his works that many Muslim scholars study is Awjaz al-Masālik Ilā Muwaththa' Mālik which is the syarah of the kitab al-Muwathta’. This study discusses the method of Muhammad Zakariyyā al-Kāndahlawiyy when interacting with hadiths that are considered mursal. This study is a literature study and uses a document analysis method with the help of ATLAS.ti software version 9.1.5.0. The results of this Study found that when Muhammad Zakariyyā al-Kāndahlawiyy interacted with the mursal hadith in the book of Awjaz al-Masālik Ilā Muwaththa' Mālik, he mentioned the status of the hadith if mursal, mentioned the cause of mursal, mentioned the reinforcing hadith of mursal hadith; if there is no reinforcement in other hadith books then he put fatwa the opinion of scholars. In general, he combines the methods of hadith scholars and fiqh scholars so that the hadiths that originally had mursal status can be used in the hadith and its fiqh.